Design and realization of motion detector system for house security - Zainab G. Faisal; Maysam Sameer Hussein; Amany Mohammad Abood (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
In this paper, the design and realization of motion detector system for house security based GSM network is presents. The development of microcontroller carried out intruder detection that supports tracking techniques to provide vital security with control and alert operation inside and outside the home. The pivot of security on the integration the motion detector and cameras into web applications has become more interested. The smart surveillance Pi camera obtain the input from the motion detector and controller which is send the video to the web server allowing the homeowner to access this video by use web applications. An intrusion alert send to the owner by mean of message via mobile and buzzers alarms located at suitable distance. This system is typify proficient video camera for remote sensing and tracking with live video for succeeding play again to offers efficient and easy implementation with omnipresent surveillance solution